Effect of marine algae as fertilizer for rice cultivation (Oryza sativa L) in Babahoyo, Ecuador - Meza Aguilar, Jorge Javier; Almeida Veintimilla , Aura Catalina (ECOAgropecuaria. Revista Científica Ecológica Agropecuaria, 2022)
The research was carried out during the winter of 2021 in the Babahoyo Canton, province of Los Ríos. The objective was to evaluate the production of rice cultivation with the application of seaweed as a complement to chemical fertilization, the planting material was the INIAP FL 1480 Cristalino variety, the treatments and doses evaluated were (T1.- 7.27 kg/ ha; T2.- 9.09 kg/ha; T3.- 10.91 kg/ha; T4.- 12.73 kg/ha and T5.- control), the applications were made to the soil at 25 and 40 days after planting. With the T3 treatment, the best results were obtained in the variables plant height 117.60 cm at 45 days; grain numbers per panicle 173.40; percentage of full/vain grains; thousand grain weight 27.18 and the highest yield 7 071.71 kg/ha-1. With the application of seaweed, it is possible to increase the yields of rice cultivation in the Babahoyo area.
Keywords: algasoil; dose; INIAP FL 1480; Yield